2018
DOI: 10.1039/c8dt02639d
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in cyclometalation: steric effects leading to competing pathways and η12-cyclometalated iridium(iii) complexes

Abstract: The iridation of (R)-N,N-dimethyl-1-(1-naphthyl)ethylamine in the presence of a base afforded an assortment of products ranging from organic molecules to coordinated systems and cyclometalated complexes. The transformation affirmed the postulation where steric effects within the coordination sphere favor a β-hydride elimination-like decomposition pathway, competing alongside ortho-metalation, thus leading to iminium intermediates. The same procedure also generated an unprecedented carbocyclic η,η-cycloiridated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In the same year, the same group carried out the reaction of ( R )‐ N,N ‐dimethyl‐1‐(1‐naphthyl)ethylamine with [IrCp*Cl 2 ] 2 , employing sodium acetate in 1,2‐dichloroethane (DCE) at reflux temperature, in order to gain more insight into the selectivity of cyclometallation [25] . This reaction generated six isolable products: cycloiridated complexes 13 , 15 , and 16 , dimethylamine coordinated complex 14 and organic molecules 1‐acetonaphthone and 1‐ethylnaphthalene, as shown in Scheme 3.…”
Section: Synthesis Of Chiral Iridacyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same year, the same group carried out the reaction of ( R )‐ N,N ‐dimethyl‐1‐(1‐naphthyl)ethylamine with [IrCp*Cl 2 ] 2 , employing sodium acetate in 1,2‐dichloroethane (DCE) at reflux temperature, in order to gain more insight into the selectivity of cyclometallation [25] . This reaction generated six isolable products: cycloiridated complexes 13 , 15 , and 16 , dimethylamine coordinated complex 14 and organic molecules 1‐acetonaphthone and 1‐ethylnaphthalene, as shown in Scheme 3.…”
Section: Synthesis Of Chiral Iridacyclesmentioning
confidence: 99%
“…In the same year, the same group carried out the reaction of (R)-N,N-dimethyl-1-(1-naphthyl)ethylamine with [IrCp*Cl 2 ] 2 , employing sodium acetate in 1,2-dichloroethane (DCE) at reflux temperature, in order to gain more insight into the selectivity of cyclometallation. [25] This reaction generated six isolable products: cycloiridated complexes 13, 15, and 16, dimethylamine coordinated complex 14 and organic molecules 1-acetonaphthone and 1-ethylnaphthalene, as shown in Scheme 3. It was suggested that the formation of 13, 14 and 1-acetonaphthone could start from a β-hydride elimination-like process, 15 could be derived from 13 via a dehydrogenation procedure, and 16 could be formed from the dehydroamination of a complexed cyclic intermediate, hydrogenation of which could produce 1-ethylnaphthalene.…”
Section: Synthesis Of Chiral Iridacyclesmentioning
confidence: 99%
See 1 more Smart Citation